Ecological carrying capacity of Cidahu Nature Tourism Object, Gunung Halimun Salak National Park - Koko Komarudin; Rosadi Rosadi; Sata Yoshida Srie Rahayu (Indonesian Journal of Applied Environmental Studies, 2022)
The nature tourism sector plays an important role in national economic growth. Cidahu Nature Tourism Object, Gunung Halimun Salak National Park (GHSNP) is one of the natural attractions that has provided many benefits for the government, especially in supporting local community's economy. Natural tourism activities in Cidahu, which have been tended for mass tourism, can both benefit the economy and have a negative impact on conservation areas. The purpose of this study was to determine the tourism carrying capacity in Cidahu Nature Tourism Object by examining the maximum number of tourists that can be accommodated so that the physical, environmental and management aspects are not damaged ecologically and tourism actors may still receive satisfaction from the activities. Through a descriptive research method, data processing techniques using the Cifuentes method was used to calculate the physical carrying capacity (PCC), real carrying capacity (RCC) and effective carrying capacity (ECC). Based on the results of the study, the physical carrying capacity value was 10,593, the real carrying capacity was 148 and the effective carrying capacity was 133. With the PCC value RCC ECC, the tourism carrying capacity in Cidahu Natural Tourism Object is still in good condition.